2011
DOI: 10.1007/978-1-4419-7028-2
|View full text |Cite
|
Sign up to set email alerts
|

Biomphalaria Snails and Larval Trematodes

Abstract: ), except for brief excerpts in connection with reviews or scholarly analysis. Use in connection with any form of information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed is forbidden. The use in this publication of trade names, trademarks, service marks, and similar terms, even if they are not identified as such, is not to be taken as an expression of opinion as to whether or not they are subject to proprietary rights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 479 publications
0
1
0
1
Order By: Relevance
“…We have shown that S. mansoni occupies an intermediate position in a trematode dominance hierarchy in B. pfeifferi in west Kenya and can be routinely displaced if present in co-infections by echinostomes and amphistomes, although particular species may vary in their predatory tendencies and the degree of their dominance (Hechinger et al, 2011; Garcia-Vedrenne et al, 2016). Surprisingly, even though much of the previous work focusing on interspecific trematode antagonism has been undertaken in the context of exploiting it as a potential control strategy for schistosomiasis (Combes, 1982; Moravec et al, 1974; Pointier and Jourdane, 2000; Toledo and Fried, 2011) ours is the first study undertaken in which all the species involved are extant in sub-Saharan Africa, where schistosomiasis assumes its greatest public health significance.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that S. mansoni occupies an intermediate position in a trematode dominance hierarchy in B. pfeifferi in west Kenya and can be routinely displaced if present in co-infections by echinostomes and amphistomes, although particular species may vary in their predatory tendencies and the degree of their dominance (Hechinger et al, 2011; Garcia-Vedrenne et al, 2016). Surprisingly, even though much of the previous work focusing on interspecific trematode antagonism has been undertaken in the context of exploiting it as a potential control strategy for schistosomiasis (Combes, 1982; Moravec et al, 1974; Pointier and Jourdane, 2000; Toledo and Fried, 2011) ours is the first study undertaken in which all the species involved are extant in sub-Saharan Africa, where schistosomiasis assumes its greatest public health significance.…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian tersebut menunjukkan bahwa salinitas yang tinggi menyebabkan berkurangnya kepadatan keong perantara schistosomiasis, sedangkan serkaria dari schistosoma masih dapat bertahan hidup. 13,14 Tinggi rendahnya infection rate serkaria S. japonicum dapat dipengaruhi oleh banyaknya hewan mamalia positif schistosomiasis sebagai sumber telur S.japonicum yang melewati daerah fokus keong tersebut. Hewan mamalia yang dimaksud bisa saja hewan liar maupun ternak milik masyarakat yang kebetulan berada di daerah fokus.…”
Section: Bahan Dan Metodeunclassified